La responsabilidad social empresarial y su influencia en la imagen de marca de la microempresa SEVA chocolate del cantón Tosagua - Basurto Arteaga, Jordan Stiven (2024)
The objective of this research was to evaluate Corporate Social Responsibility (CSR) and its influence on the Brand Image (IM) of the SEVA Chocolate microenterprise in the Tosagua canton. Three methodological phases were completed: in the first stage, a diagnosis of the CSR practices of the microenterprise was carried out, through the application of an interview validated by the expert method of Hernández Nieto, after identifying indicators through a bibliographic review. and selection thereof using Aiken's V coefficient; Next, a survey with a Likert scale was developed, and it was validated like the interview, from which it was applied to the clients of the microenterprise, whose data were processed in the SPSS Software, determining the reliability of the data through Cronbach's Alpha, in addition to establishing correlations between variables through the Pearson Test; In the third phase, a proposal for strategic CSR actions was developed for the MI of the microenterprise, complying with each stage of the PHVA cycle. The results indicate deficiencies in the company's CSR and IM, mainly in practices such as: elaboration of strategic and marketing direction with a social focus, as well as attention to policies and measurement of customer satisfaction regarding the reputation of the brand. A strong and positive impact is concluded between CSR on the IM of the microenterprise, as well as in each of its indicators.